2022
DOI: 10.3390/plants11101383
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Anti-Photoaging and Skin Protective Effects of Licania macrocarpa Cuatrec Methanol Extract

Abstract: The Licania genus has been used in the treatment of dysentery, diabetes, inflammation, and diarrhea in South America. Of these plants, the strong anti-inflammatory activity of Licania macrocarpa Cuatrec (Chrysobalanaceae) has been reported previously. However, the beneficial activities of this plant on skin health have remained unclear. This study explores the protective activity of a methanol extract (50–100 μg/mL) in the aerial parts of L. macrocarpa Cuatrec (Lm-ME) and its mechanism, in terms of its moistur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 53 publications
1
2
0
Order By: Relevance
“…Therefore, the degradation of ECM caused by aging is alleviated by Mb-ME, and skin elasticity is improved. Meanwhile, as reported, UVB activates the generation of inflammatory mediators, leading to an increase in chronic inflammation and inflammatory aging [37]. This is verified by comparing the aforementioned to HaCaT cells without UVB treatment (Figure 2B,C).…”
Section: Discussionsupporting
confidence: 83%
“…Therefore, the degradation of ECM caused by aging is alleviated by Mb-ME, and skin elasticity is improved. Meanwhile, as reported, UVB activates the generation of inflammatory mediators, leading to an increase in chronic inflammation and inflammatory aging [37]. This is verified by comparing the aforementioned to HaCaT cells without UVB treatment (Figure 2B,C).…”
Section: Discussionsupporting
confidence: 83%
“…HA is a dominant moisturizing macromolecule in the skin, with distribution in both dermis and epidermis. 24 When encountering UVB exposure, epidermal and dermal cells of human skin produce and secrete a certain amount of HA as a natural anti-photoaging response. The UVB irradiation increased the production of HA by 3T3 cells (Figure 4C).…”
Section: Retinoid Treatment Attenuated Uvb-induced Mmp Upregulation A...mentioning
confidence: 99%
“…In modern clinical practice, honeysuckle has several medicinal benefits, such as the treatment of arthritis, diabetes mellitus, fever, infections, sores, and swelling [ 2 , 3 ]. Pharmacological studies have shown that extracts of honeysuckle have a broad spectrum of biological activity, including antioxidant [ 4 , 5 ], antibacterial [ 6 ], anti-inflammatory [ 7 ], antiphotoaging [ 8 ], antinociceptive [ 9 ], antiangiogenic [ 10 ], antipyretic [ 11 ], antiviral [ 12 , 13 ], and hepatoprotective effects [ 14 ]. A number of chemical components with diverse structures, such as iridoids, flavonoids, saponins, polyphenols, and cerebrosides, have been isolated from this TCM [ 15 ].…”
Section: Introductionmentioning
confidence: 99%